2018
DOI: 10.1007/s10068-018-0510-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for change in microbial contents in five mixed Kimchi starter culture and commercial lactic acid bacterial-fermented sausages and biological hazard in manufacturing facilities

Abstract: The purpose of this study was to compare change in microbial contents between sausages with five mixed Kimchi starter culture (T1) and commercial lactic acid bacterial (LAB) (T2) during fermentation, and to screen manufacturing facilities for microbial condition. For T1 and T2, pH levels decreased at 7 days and increased at 14 days. For color, the lightness of T1 decreased at 7 days (36.50 ± 6.04) and slightly increased at 14 days (38.40 ± 4.35). In addition, T1 and T2 were observed decrement of redness and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…As shown in Figure 3C , the b* values in both groups presented an increasing trend, compared to 0 days, the b* values in the SBM-52 sausages and the L-S sausages raised to 9.10 and 9.85, respectively, over the thirteen-day ripening. The increase in b* values could be explained by lipid oxidation ( Lee et al, 2019 ; Liu et al, 2019 ). Although the a* value in L-S was lower than that in SBM-52 and the b* value was higher than that in SBM-52, there was no significant difference ( p > 0.05) among the two groups at 13 days of ripening.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3C , the b* values in both groups presented an increasing trend, compared to 0 days, the b* values in the SBM-52 sausages and the L-S sausages raised to 9.10 and 9.85, respectively, over the thirteen-day ripening. The increase in b* values could be explained by lipid oxidation ( Lee et al, 2019 ; Liu et al, 2019 ). Although the a* value in L-S was lower than that in SBM-52 and the b* value was higher than that in SBM-52, there was no significant difference ( p > 0.05) among the two groups at 13 days of ripening.…”
Section: Resultsmentioning
confidence: 99%
“…The most popular microbial hurdles in the studies included in this review were combined starter cultures applied to meat [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The use of a mixture of non-starter protective cultures to inhibit spoilage bacteria or/and foodborne pathogens was also assessed [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the included studies, a starter culture composed of at least two LAB strains was used by Lee et al (2018) [ 39 ], Olaoye et al (2010) [ 43 ], Olaoye et al (2011) [ 44 ], Olaoye et al (2015) [ 45 ], Iacumin et al (2020) [ 36 ], and Vatanyoopaisarn et al (2011) [ 51 ] ( Table 1 ). In the study by Iacumin et al (2020) [ 36 ], two different bioprotective mixed cultures consisting of lactic acid bacteria were used against L. monocytogenes bacteria that were intentionally inoculated into cooked cubed ham, which was packaged in modified atmosphere packaging (MAP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, they are characterized by good microbiological, chemical, and sensory qualities (Anna et al, 2019; Chlebowska‐Smigiel et al, 2017). Many studies have shown that the starter culture can influence the nitrite concentration in Chinese pickled vegetables (Jung et al, 2019; Lee et al, 2019; J. Zhang et al, 2022) and meat products (Chen et al, 2016; Paik & Lee, 2014). Lactic acid bacteria (LAB) was recognized by the FAO and WHO as the only bacteriocin preservative used in food as early as 1969.…”
Section: Introductionmentioning
confidence: 99%